The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1139/f90-041
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Migration in Daphnia galeata mendotae (Brooks): Demographic Responses to Changes in Planktivore Abundance

Abstract: 1990. Vertical migration in Daphnia galeata mendotae (Brooks): demographic responses to changes in planktivore abundance. Can. 1. Fish. Aquat. Sci.47: 395400.We tested the hypothesis that changes in vertical migration patterns in Baphnid gsledta rnendstde were correlated with changes in planktivore numbers. A 4-yr data set from bake St. George showed that during 1982, when planktivores numbered approximately 2500-ha-', adult D. galeata mendstag were tsund in the epilimnion at both midday and midnight. During 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…Holopedium is a generally poor competitor that has low clearance rates (Allan 1973;Hessen et al 1993;Brett and Goldman 1994). D. galeata mendotae uses vertical migration to avoid predation (Stirling et al 1990;Lehman and Caceres 1993;Schulz and Yurista 1998), which could effectively result in a vertical separation of resource use between Conochilus and D. galeata mendotae. Dumitru et al (2001) reported that owing to vertical migration, there is only weak overlap between Bythotrephes and D. galeata mendotae in Harp L., as D. galeata mendotae remains in deep waters for large portions of the day.…”
Section: Discussionmentioning
confidence: 99%
“…Holopedium is a generally poor competitor that has low clearance rates (Allan 1973;Hessen et al 1993;Brett and Goldman 1994). D. galeata mendotae uses vertical migration to avoid predation (Stirling et al 1990;Lehman and Caceres 1993;Schulz and Yurista 1998), which could effectively result in a vertical separation of resource use between Conochilus and D. galeata mendotae. Dumitru et al (2001) reported that owing to vertical migration, there is only weak overlap between Bythotrephes and D. galeata mendotae in Harp L., as D. galeata mendotae remains in deep waters for large portions of the day.…”
Section: Discussionmentioning
confidence: 99%
“…Of the several hypotheses put forth to explain the adaptive significance of DVM (Kerfoot, 1985;Lampert, 1989), evidence implicating predator evasion has recently accumulated from field (Bollens & Frost, 1989a;Stirling et al, 1990;Ohman, 1990), theoretical (Frost, 1988;Gabriel & Thomas, 1988;Mange1 & Clark, 1988;Ohman, 1990) and experimental (Bollens & Frost, 1989b;Neill, 1990) studies. These studies lead to the prediction that the occurrence of DVM in planktonic animals in the field is positively related to the abundance of their predators.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous abiotic and biotic factors have been proposed to explain DVM behaviour . Avoidance of visual predators, such as planktivorous fish, is now considered to be the major process causing DVM both in marine (Bollens & Frost, 1989a, 1989bFrost & Bollens, 1992) and freshwater zooplankton (Wright et al, 1980 ;Stich & Lampert, 1981 ;Gliwicz, 1986 ;Stirling et al, 1990 ;Lampert, 1992 ;De Stasio, 1993) . Other factors that have been found to initiate and regulate zooplankton DVM include light (Ringelberg, 1987, Dodson, 1990Leibold & West, 1993), temperature (Gerritsen, 1982), invertebrate predation and food distribution (Geller, 1986 ;Pijanowska & Dawidowicz, 1987 ;Leibold, 1990) .…”
Section: Introductionmentioning
confidence: 99%